Penerapan Metode Outdoor Study Untuk Meningkatkan Hasil Belajar IPA - Ali, Ramsah; abdussyukur, abdussyukur; Ali, Musfirah (Jumper: Journal of Educational Multidisciplinary Research, 2023)
The purpose of this study is to improve student learning outcomes through the application of outdoor study methods in improving the learning outcomes of fourth-grade in MI Negeri 2 Central Aceh. The type of research used is a quantitative research type of Class Action Research (PTK) with a quantitative descriptive approach). The object of this research is the students of Class 4 MI Negeri 2 with a total of 27 students consisting of 8 female students and 19 males. The data collection technique in this study is test. Data analysis techniques using quantitative descriptive. The results of this study showed that with the Outdoor Study method, there was a pleasant atmosphere so that student learning outcomes increased, namely from cycle I, cycle II and cycle III there was an increase, in cycle I the number of students who received complete grade was 9 students or 33.3%, incomplete grade in cycle I was 18 students or 66.67%, Cycle II occurred complete grade was 15 students or 55.6%, incomplete grade were 12 students or 55.6%. While in the third cycle, there is an increase in the complete score of 25 students 92.6%. It was concluded that the Outdoor Study method can improve student learning outcomes in science learning.